Noma: a neglected tropical disease - Mirta Hediyati Reksodiputro; Mikhael Yosia (Oto Rhino Laryngologica Indonesiana, 2021)
Background: Noma is an orofacial gangrene often manifesting in malnourished children in developing and tropical countries. Epidemiological data on noma are hard to find, but it is estimated that the global incidence of noma is 30-40,000 cases per year, with estimated mortality rate of about 85%. Purpose: To discuss the pathogenesis, diagnosis, prevention, and treatment of noma. Literature review: The cause of noma is multifactorial, but is often found in conjunction with malnutrition and with other diseases such as measles, malaria, and the human immunodeficiency virus (HIV), along with poor oral hygiene. The pathogenesis of noma includes a rapidly spreading noninfectious gangrene infection of the face, often preceded by acute necrotizing gingivitis, and stomatitis. Microbiological studies show opportunistic infections caused by imbalance of normal intraoral microorganisms. The key to prevention is to increase food hygiene, improving vaccination program against measles, prevention of malaria and HIV, and early detection and treatment of necrotic gingivitis and stomatitis. Early treatment with antibiotics can prevent gangrene formation or reduce the extent of the lesions. Late treatment consists of surgical rehabilitation, which is often hard to conduct. Conclusion: Noma is an infectious disease that can cause wide gangrenous wounds. Recognizing and understanding the symptoms and characteristic signs of noma is important so that comprehensive prevention and management can be given as early and optimally as possible to provide complete recovery for patients.ABSTRAK Latar belakang: Noma adalah gangren orofasial yang menyerang anak-anak kekurangan gizi terutama di negara-negara berkembang dan negara-negara tropis. Data epidemiologi tentang noma sangat langka, tetapi perkiraan kejadian global saat ini adalah 30-40.000 kasus per tahun, dengan tingkat kematian sekitar 85%. Tujuan: Membahas patogenesis, diagnosis, pencegahan, dan tatalaksana noma. Tinjauan pustaka: Penyebab noma multifaktorial, namun sering ditemukan bersamaan dengan malnutrisi dan dengan penyakit lain seperti campak, malaria, dan human immunodeficiency virus (HIV). Sering pula terjadi bersamaan dengan higiene mulut yang buruk. Patogenesis noma meliputi infeksi gangren tidak menular, yang menyebar cepat di daerah wajah, sering didahului oleh gingivitis nekrotikans akut, dan stomatitis. Studi mikrobiologi menunjukkan adanya infeksi oportunistik yang disebabkan oleh ketidakseimbangan mikroorganisme intraoral normal. Pencegahan dapat berupa nutrisi yang baik, vaksinasi campak, pencegahan malaria dan HIV, termasuk deteksi dini dan pengobatan gingivitis nekrotikans dan stomatitis. Pengobatan dini dengan antibiotik dapat mencegah terjadinya gangren atau mengurangi luasnya lesi. Perawatan lebih lanjut berupa rehabilitasi bedah, yang seringkali tidak mudah dilakukan. Kesimpulan: Noma adalah penyakit infeksi yang dapat menimbulkan defek luka gangren luas. Penting untuk mengenali dan memahami gejala serta tanda karakteristik noma, sehingga pencegahan dan tatalaksana secara komprehensif dapat diberikan sedini dan seoptimal mungkin, agar dapat memberikan kesembuhan sempurna untuk pasien.Kata kunci: noma, penyakit tropik terabaikan, gangren orofasial, gingivitis nekrotik akut